PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DAN PENILAIAN DIRI BERBASIS METAKOGNISI UNTUK STATISTIKA ELEMENTER - ISRA NURMAI YENTI; Dona Afriyani; Susi Herawati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
This research was aimed at developing valid lesson plans and metacognition-based self evaluation in Statistika Elementer subject. Learning strategies that encouraged students’ metacognition were problem-based learning and think pair share. This research employed Research and Development design. There were two main stages in this research: need analysis and prototype design. Need analysis was began with interviewing colleague, analyzing syllabus and lesson plans, analyzing students’ characteristics, analyzing lesson plan literature, self evaluation and metacognition. Prototype design referred to need analysis. Three experts recommended that lesson plans and self evaluation were valid both in terms content and construct.